2023
DOI: 10.1038/s41392-023-01344-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of allergic diseases and implications for therapeutic interventions

Abstract: Allergic diseases such as allergic rhinitis (AR), allergic asthma (AAS), atopic dermatitis (AD), food allergy (FA), and eczema are systemic diseases caused by an impaired immune system. Accompanied by high recurrence rates, the steadily rising incidence rates of these diseases are attracting increasing attention. The pathogenesis of allergic diseases is complex and involves many factors, including maternal-fetal environment, living environment, genetics, epigenetics, and the body’s immune status. The pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 533 publications
1
41
0
7
Order By: Relevance
“…A hypothesis that individuals with pre-existing respiratory allergy might have a higher likelihood of developing anaphylactic or non-anaphylactic responses post-COVID-19 vaccination has been considered [16][17][18]. A tolerance study with the BNT162 mRNA vaccine conducted by Nittner-Marszalska et al in 2021 [19] reported a higher duration of systemic adverse effects in allergic patients in addition to a higher frequency of local reactions, headaches, and nausea, as was described elsewhere [20]. An exacerbation of the clinical picture of asthma has been reported after vaccination with an inactivated virus-based COVID-19 vaccine [21], but there are limited studies with a large number of patients focused on respiratory allergies as a side effect.…”
Section: Introductionmentioning
confidence: 98%
“…A hypothesis that individuals with pre-existing respiratory allergy might have a higher likelihood of developing anaphylactic or non-anaphylactic responses post-COVID-19 vaccination has been considered [16][17][18]. A tolerance study with the BNT162 mRNA vaccine conducted by Nittner-Marszalska et al in 2021 [19] reported a higher duration of systemic adverse effects in allergic patients in addition to a higher frequency of local reactions, headaches, and nausea, as was described elsewhere [20]. An exacerbation of the clinical picture of asthma has been reported after vaccination with an inactivated virus-based COVID-19 vaccine [21], but there are limited studies with a large number of patients focused on respiratory allergies as a side effect.…”
Section: Introductionmentioning
confidence: 98%
“…[6][7][8][9] Notably, plasma proteins are closely associated with allergic diseases such as asthma. 10,11 Genetic variants associated with plasma protein levels have been identified by genome-wide association studies (GWAS) and are defined as "protein quantitative trait loci (pQTLs)." 12,13 PQTLs provide an opportunity to utilize Mendelian randomization (MR) methods in investigating the causal effects of potential drug targets on human disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between childhood asthma-associated proteins and other disease outcomes revealed by PheWAS analysis.WU ET AL.-7 of10 developed for the treatment of respiratory disorders, such as asthma and COPD. Cilomilast is orally active and functions as a selective phosphodiesterase-4 inhibitor.…”
mentioning
confidence: 99%
“…The pathogenesis involves a shift of the immune system from a T helper (Th) 1 to a Th2-dominant response. 1 The development of the immune system begins in fetal life and continues in the neonatal period, when the immune response is characterized by Th2 dominance. However, with increasing postnatal contact with different pathogens, the immune response normally shifts toward a Th1-type response.…”
Section: Introductionmentioning
confidence: 99%